Heavy Metals Concentration and Possible Health Risks From Shrimp Nurseries at South-West Region, Bangladesh (Bangladesh Journal of Zoology, 2020)
Water pollution poses a threat of heavy metal accumulation in aquatic animals. This study was designed to determine the heavy metals contamination in shrimp PL (post larvae) nurseries of Khulna region and associated human health risks. Water (raw sea water, treated and outlet water) and PL samples of five shrimp nurseries of Khulna districts were analyzed to measure the concentrations of six heavy metals (Zn, Cr, Mn, Cu, Pb and Ni) by using Atomic Absorption Spectrometer (Model No: AA-7000, Shimadzu). The metal concentrations were higher in almost all PL samples of five nurseries except Mn, which value was below detection level (BDL). Concentrations of Zn and Cu were significantly higher (PCu>Pb>Cr>Ni>Mn. The target hazard quotients (THQ) of PL samples were followed the rank Pb>Cu>Zn>Ni>Cr>Mn. Target cancer risk (TR) of Pb of nursery-2 PL for rural people was 1.1305 × 10-4 while the urban and average TR was 1.4757× 10-4 and 1.2195× 10-4, respectively. The findings of the present study on heavy metal concentrations in PL nurseries indicate the necessities of quality water for prevention of accumulation heavy metals further in shrimp grown-up stages. Proper management strategies should be taken to avoid this risk.Bangladesh J. Zool. 48(1): 167-179, 2020